Physical Activity on Prescription (PAP), in patients with metabolic risk factors. A 6-month follow-up study in primary health care - Lundqvist, Stefan (PLoS One, 2017)
There is strong evidence that inadequate physical activity (PA) leads to an increased risk of lifestyle-related diseases and premature mortality. Physical activity on prescription (PAP) is a method to increase the level of PA of patients in primary care, but needs further evaluation. The aim of this observational study was to explore the association between PAP-treatment and the PA level of patients with metabolic risk factors and the relationship between changes in the PA level and health outcomes at the 6 month follow-up. This study included 444 patients in primary care, aged 27–85 years (56% females), who were physically inactive with at least one component of metabolic syndrome. The PAP-treatment model included: individualized dialogue concerning PA, prescribed PA, and a structured follow-up. A total of 368 patients (83%) completed the 6 months of follow-up. Of these patients, 73% increased their PA level and 42% moved from an inadequate PA level to sufficient, according to public health recommendations. There were significant improvements (p≤ 0.05) in the following metabolic risk factors: body mass index, waist circumference, systolic blood pressure, fasting plasma glucose, cholesterol, and low density lipoprotein. There were also significant improvements regarding health-related quality of life, assessed by the Short Form 36, in: general health, vitality, social function, mental health, role limitation-physical/emotional, mental component summary, and physical component summary. Regression analysis showed a significant association between changes in the PA level and health outcomes. During the first 6-month period, the caregiver provided PAP support 1–2 times. This study indicates that an individual-based model of PAP-treatment has the potential to change people’s PA behavior with improved metabolic risk factors and self-reported quality of life at the 6 month follow-up. Thus, PAP seems to be feasible in a clinical primary care practice, with minimum effort from healthcare professionals.